2017
DOI: 10.1038/tp.2016.292
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects influencing risk for major depressive disorder in China and Europe

Abstract: Major depressive disorder (MDD) is a common, complex psychiatric disorder and a leading cause of disability worldwide. Despite twin studies indicating its modest heritability (~30–40%), extensive heterogeneity and a complex genetic architecture have complicated efforts to detect associated genetic risk variants. We combined single-nucleotide polymorphism (SNP) summary statistics from the CONVERGE and PGC studies of MDD, representing 10 502 Chinese (5282 cases and 5220 controls) and 18 663 European (9447 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 39 publications
2
54
2
4
Order By: Relevance
“…For comparison, however, the trans-ethnic correlation for recurrent MDD is 0.41 (Bigdeli et al 2017), thus the magnitudes of our observed correlations are not unexpected. Findings for the non-melancholic MDD subtype further support the hypothesis that genetic factors are common across more severe psychopathologies.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For comparison, however, the trans-ethnic correlation for recurrent MDD is 0.41 (Bigdeli et al 2017), thus the magnitudes of our observed correlations are not unexpected. Findings for the non-melancholic MDD subtype further support the hypothesis that genetic factors are common across more severe psychopathologies.…”
Section: Discussionmentioning
confidence: 58%
“… a Within-PGC results obtained from Cross-Disorder Group of the Psychiatric Genomics Consortium (2013) b Within-PGC results obtained from Cross-Disorder Group of the Psychiatric Genomics Consortium et al (2013) c PGC–CONVERGE results obtained from Bigdeli et al (2017) …”
Section: Figmentioning
confidence: 99%
“…MDD also shows substantial heritability (approx. 0.37) [9, 10] and polygenic inheritance [11, 12]. However, promis ing genetic risk candidates for SCZ and MDD had not been well implicated until the emergence of recent large-scale genome-wide association studies (GWAS) [13-21].…”
Section: Introductionmentioning
confidence: 99%
“…However, there was generally only modest support for shared genetic effects between Hispanics/Latinos and European Americans as shown in the analyses examining more SNPs or aggregate polygenic variation as measured through a genetic risk score. Prior trans-ethnic analyses of MDD have also suggested possible population differences in genetic liability to depression across racial/ethnic groups (Bigdeli et al, 2017). The lack of observed overlap in genetic risk factors for depression across ancestry groups could be due to low power in our sample.…”
Section: Discussionmentioning
confidence: 99%